Bacteriological profile of chronic suppurative otitis media in a tertiary care hospital - Rangaiah, Sowmya Tumkur; Dudda, Ravi; Prasad, M. Hanumanth; Balaji, Nagavara Kalegowda; B., Sumangala; Gudikote, Madhuri Mruthyunjaya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Chronic suppurative otitis media is a disease affecting the middle ear and mastoid cavity, leading to considerable morbidity by causing hearing loss; and even life threatening complications in squamosal type of CSOM, if left untreated over long periods of time. Hence it is imperative to treat the persistent ear discharge in CSOM according to the antibiotic susceptibility of the organisms isolated. Methods: This is a prospective cross sectional study done in 135 patients of chronic suppurative otitis media presenting with active ear discharge. Sterile swabs were used to collect pus from discharging ear and sent for culture sensitivity. Results: Staphylococcus and Pseudomonas aeruginosa were the most common organisms isolated in this study. Pseudomonas aeruginosa was most sensitive to Piperacillin-Tazobactam, followed by Meropenem and Ciprofloxacin. Staphylococcus aureus was most sensitive to Linezolid followed by Cefoxitin and Erythromycin. Conclusions: Treating active discharge of CSOM according to pus culture sensitivity pattern reduces the bacterial load in the middle ear and makes the ear more favourable for graft uptake. Keywords: Chronic suppurative otitis media, Aerobic bacterial culture, Antibiotic susceptibility, Pseudomonas aeruginosa, Staphylococcus aureus